Green manure and soil management systems on cotton yield - Carvalho, Marco Antonio Camillo de; Athayde, Manoel Luiz Ferreira; Soratto, Rogério Peres; Alves, Marlene Cristina; Sá, Marco Eustáquio de (Pesquisa Agropecuaria Brasileira, 2004)
The adoption of conservation management system and succession of crops after green manures aim at preserving the environment and soil quality, without dispensing the largest cash crop yield. The objective of this work was to evaluate the effects of soil management systems and green manures on cotton yield (Gossypium hirsutum L.). The experiment was carried out in a Typic Hapludox, covered by Savannah vegetation. The experimental design used was that of randomized blocks, in a split plot scheme, with four replications. In plots, four green manures were used: black velvet bean, pigeon pea, sunn hemp, millet and fallow area (spontaneous vegetation). In subplots, two managament soil systems were used: no-tillage and conventional tillage (one disk harrow + two levelling harrow). Soil management systems do not affect cotton yield. Previously green manures do not affect cotton yield grown in succession, both in no-tillage and conventional tillage systems.